Clinical associations between gout and multiple sclerosis, Parkinson’s disease and motor neuron disease: record-linkage studies - Pakpoor, Julia (BMC Neurol, 2015)
BACKGROUND: Uric acid has antioxidant effects on neurons. Abnormally high levels of uric acid are, however, associated with gout. Previous studies have suggested that high levels of uric acid (and the presence of gout) may exert a protective effect against the risk of developing some neurological diseases. We aimed to investigate this hypothesis in a large database of hospital admissions in England. METHODS: We analysed a database of linked statistical records of hospital admissions and death registrations in England (1999–2012). A cohort of people with gout was constructed and followed for development of multiple sclerosis (MS), Parkinson’s disease (PD) or motor neuron disease (MND). Then, conversely, cohorts of all people in the database with MS, PD or MND were constructed and followed for subsequent gout. Rate ratios (RRs) were determined, comparing these cohorts with people in a reference cohort. RESULTS: In the gout cohort, we observed a modest elevation of the overall risk of subsequent MS, PD and MND (respectively, RR = 1.27 (95% confidence interval 1.03-1.55), 1.11 (1.05-1.17) and 1.28 (1.11-1.48) which was largely attributable to an increased risk observed in the early years after hospitalisation for gout. The increased risk of neurological disease did not remain after 5 years. In the cohorts of people with MS or PD, there was a significantly reduced risk of subsequent gout admission (RR = 0.79 (0.69-0.89) and 0.83 (0.79-0.87), respectively). This inverse association was sustained over time. There was also a reduced risk of MND following gout which only emerged more than five years following initial gout admission (RR at 5+ years 0.35 (0.15-0.68)). CONCLUSIONS: This study investigated the epidemiological evidence for a protective role of high serum concentration of uric acid, for which we used gout as a proxy, in the aetiology of MS, PD or MND. Our observations do not support this hypothesis. However, when the order was reversed, and we retrospectively followed up patients with MS, PD and MND for a number of years, we found a statistically significant deficit of gout. This suggests that there is relationship between some aspects of these neurodegenerative diseases and metabolism of uric acid.